Modelagem de processos de negócio em uma empresa do setor de informática - Pontes, Beatriz Lima Gê (Universidade Federal Rural do Semi-Árido, 2018)
Any and all organization around its activities to fulfill its purpose. The set of this activities is called process. From this assumption, it is inferred that every organization is organized around the execution of processes, whether they had structured or not, whether they had known or not. This study aims to analyze the critical process of a company in the IT sector through process modeling in BPMN - Business Process Model and Notation - in order to visualize the process as a whole, identify its failures and propose improvements that are aligned with the company's organizational objectives. For this, this case study of descriptive character had the means of investigation observation and interview. The results point out that it is possible to establish improvements and standardize the process by modeling its current state and its future state, and that the process analyzed is applicable considering the structure of the company, its opportunities and intention to use it.
Monografia
Keywords: Gestão de Processos de Negócio; Modelagem de Processos de Negócio; Processos de Negócio; Business Process Management; Business Processes Modeling; Business Processes; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO